UPAYA MENINGKATKAN KETERAMPILAN MENULIS PENGUMUMAN DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS V SD KRISTEN 03 EBEN HAEZER SALATIGA - Rhiki Darmawan; Herry Sanoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to improve the writing skills of announcement material by using the Problem Based Learning (PBL) learning model for fifth grade students of Eben Haezer Salatiga Christian Elementary School 03. This class action research was conducted in two cycles. Each cycle consists of one meeting and four stages, namely planning, implementation, observation, and reflection. In this study, researchers used observation sheets and learner worksheets. The data obtained from this study were analyzed in the form of percentages. From the scores of announcement writing skills of fifth grade students of Eben Haezer Salatiga Christian Elementary School 03, there was an increase in cycle II. The results of this study have increased from cycle I to cycle II, as evidenced by the value of announcement writing skills with a percentage of 46% in cycle I to 84% in cycle II.